Implementation of Clean and Healthy Living Behavior among Elementary School Students: An Overview - Setiawan, Dani; Nurapandi, Adi; Waluyo, Endrian Mulyady Justitia (Genius Journal, 2024)
Introduction: Clean and Healthy Living Behavior (PHBS) among elementary school students plays a critical role in fostering lifelong health habits and preventing communicable diseases within school environments. This overview examines the implementation, challenges, and outcomes of PHBS practices among elementary school students, highlighting their impact on overall well-being and academic performance.. Objective:  To evaluate the implementation and impact of Clean and Healthy Living Behavior practices among elementary school students, focusing on their role in promoting health and preventing diseases within the school environment. Methods: This study employed a cross-sectional design to examine the Clean and Healthy Living Behavior  among students. The population consisted of all students in Mulyajaya, Sumedang Regency, with a total sampling technique utilized for participant selection. Data collection was conducted over a period from March 2 to May 2. The data were analyzed using frequency and percentage distribution, processed with the Statistical Package for the Social Sciences (SPSS) software. Result: The results of the study showed that 10 respondents (22.7%) were categorized as having moderate behavior, 34 respondents (77.3%) were categorized as having poor behavior, and no respondents (0%) were categorized as having good behavior regarding clean and healthy living practices. Conclusion:  The findings indicate that the majority of elementary school students exhibit poor behavior regarding clean and healthy living practices (PHBS), with no students demonstrating good behavior. This underscores a critical need for targeted interventions to improve PHBS awareness and practices among this population. These results highlight the importance of implementing structured health education programs in schools to promote better PHBS behaviors. School-based interventions, involving teachers, parents, and healthcare professionals, can play a pivotal role in fostering long-term healthy habits and preventing disease transmission among students.